(untitled) (EAAE Annual Conference Proceedings, 2025)
In a world marked by uncertainty, instability, and sudden upheavals, architecture – especially architectural education – is compelled to lead the way in addressing the profound questions confronting our society and built environments. In this context, the mission of our network association, which fosters dialogue, innovation, and collaboration to advance the quality of architectural education across Europe and beyond, assumes paramount importance. The themes of this year’s European Association for Architectural Education Annual Conference, Transhistorical Pedagogies, invite us to challenge the traditional boundaries of architectural education. Through topics such as Architecture as Synthesis, No Demolish, Learning from Archives, and Skills and Crafts, we are encouraged to strike a balance between tradition and transformation, explore sustainable approaches, cultivate critical thinking and craftsmanship, challenge prevailing conventions, and embrace novel perspectives in pedagogy and research. Together, we have the opportunity to reimagine architectural education as a catalyst for innovation and critical reflection – a space where the next generation of professionals can engage with both the past and the future in meaningful ways.